2018
DOI: 10.1177/1120672118804079
|View full text |Cite
|
Sign up to set email alerts
|

Management of diabetic macular edema patients in clinical practice in Spain

Abstract: Purpose: Diabetic macular edema is the main cause of blindness in diabetic patients. Vascular endothelial growth factor is involved in diabetic macular edema pathogenesis. Vascular endothelial growth factor inhibitors are an important option in diabetic macular edema therapy. This survey investigates actual clinical practice in diabetic macular edema in Spain. Methods: An expert advisory panel of 17 Spanish ophthalmologists developed a 30-item anonymous questionnaire about diagnosis, treatment, and follow-up i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…7 The results of a survey, which analyzed the current trends of diagnosis, treatment, and follow-up of DME in Spain, showed that the 96.4% who responded to the survey considered anti-VEGF as the first treatment. 8 However, despite the good functional and anatomical outcomes obtained with the anti-VEGF therapies, many patients do not adequately respond. [9][10][11][12] According to the results of the Diabetic Retinopathy Clinical Research Network (DRCR.net) study, approximately 40% of eyes receiving ranibizumab had persistent DME at 2 years.…”
Section: Introductionmentioning
confidence: 99%
“…7 The results of a survey, which analyzed the current trends of diagnosis, treatment, and follow-up of DME in Spain, showed that the 96.4% who responded to the survey considered anti-VEGF as the first treatment. 8 However, despite the good functional and anatomical outcomes obtained with the anti-VEGF therapies, many patients do not adequately respond. [9][10][11][12] According to the results of the Diabetic Retinopathy Clinical Research Network (DRCR.net) study, approximately 40% of eyes receiving ranibizumab had persistent DME at 2 years.…”
Section: Introductionmentioning
confidence: 99%
“…Intravitreal treatment with corticosteroids (dexamethasone, fluocinolone acetonide) and anti-vascular endothelial growth factor (anti-VEGF) is now the first-line therapy for DME involving the central macula [4][5][6]. In current clinical practice in Spain, most specialists (96.4%) choose an anti-VEGF agent such as aflibercept, ranibizumab or bevacizumab (off label) as first-line therapy [7].…”
Section: Introductionmentioning
confidence: 99%
“…While in the Diabetic Retinopathy Clinical Research Network (DRCR.net) study by Wells et al 5 The patient outcomes did not differ for ranibizumab and aflibercept at 2 years, patient outcome was better at 1 year for aflibercept for those with worse visual acuity at the start of treatment. Indeed, as the authors mentioned 69.4% of doctors in a Japanese survey used aflibercept as first-line treatment, 1 it would have been interesting to know whether the specialists in the survey used visual acuity at the start of treatment as stratifying factor to choose between ranibizumab and aflibercept. 3.…”
mentioning
confidence: 99%
“…Dear Editor, I read with interest the article by Abreu-Gonzalez et al 1 titled "Management of diabetic macular edema patients in clinical practice in Spain. "…”
mentioning
confidence: 99%